Microbead layered composite metal hydroxide composite material as well as preparation method and application thereof
By covering the layered composite metal hydroxide on the surface of the microbeads, forming the microbead layered composite metal hydroxide composite material, the problem of serious stacking of layered composite materials in the prior art is solved, and better dispersion performance and corrosive anion capture effect are achieved.
Patent Information
- Application Number
- CN202311370312.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-20
- Publication Date
- 2025-04-22
AI Technical Summary
Due to the severe stacking of existing layered composite metal hydroxides, the specific surface area is small, and the effect of capturing erosive anions is suppressed.
By covering the layered composite metal hydroxide on the surface of the microbeads, a microbead layered composite metal hydroxide composite is formed, and the microbeads are used to improve the dispersion performance of the layered composite and the ability to capture corrosive anions.
The specific surface area and dispersion properties of layered composite metal hydroxides are improved, and their ability to capture corrosive anions such as chloride ions is enhanced. At the same time, it provides good anticorrosion performance and thermal insulation effects in anticorrosion coatings.
Smart Images

Figure CN119859429A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of layered composite metal hydroxides, and in particular to a microbead layered composite metal hydroxide composite material and a preparation method and application thereof. Background Art
[0002] Layered composite metal hydroxides (LDHs), also known as hydrotalcites, have a three-dimensional crystal structure formed by the longitudinal orderly extension of nano-scale octahedral two-dimensional layers. The layers are composed of two or more divalent and trivalent metal hydroxides. The anions between the layers are used to make up for the charge balance of the layers. The interlayer anions of LDHs are exchangeable and are replaced by other anions during the preparation process, so that they are used as carriers of corrosion inhibitors. In the process of corrosion protection, the corrosion inhibitor anions contained in the LDHs interlayer are released by the stimulation of external corrosive media, and can capture corrosive anionic substances, such as Cl - , SO4 2- etc.; Studies have shown that layered composite metal hydroxides can embed corrosion inhibitor ions into the interlayers of layered composite metal hydroxides through ion exchange reactions and use them as containers for corrosion inhibitors. When corrosive anions corrode, the corrosive anions in the environment and the corrosion inhibitor anions between the layers undergo ion exchange, and the corrosive anions gradually release the corrosion inhibitors, thereby inhibiting corrosion. Therefore, layered composite metal hydroxides can be used as fillers for metal anti-corrosion coatings, and have a good effect on metal corrosion prevention.
[0003] However, the layered composite metal hydroxides prepared so far all have serious stacking problems, which results in a small specific surface area and inhibits their ability to capture corrosive anions. However, microbeads have the characteristics of high hardness, high wear resistance, acid and alkali resistance, and chemical stability, and are usually used as fillers for polymers, rubbers, and coatings. Summary of the invention
[0004] The purpose of the present invention is to overcome the serious problem of stacking of layered composite metal hydroxides in the prior art, and to provide a microbead layered composite metal hydroxide composite material. The microbead layered composite metal hydroxide composite material has the properties of large specific surface area and easy dispersion, and can be used in anti-corrosion materials. At the same time, the preparation method of the microbead layered composite metal hydroxide composite material is simple in process and green and environmentally friendly.
[0005] In order to achieve the above-mentioned object, the present invention provides a microbead layered composite metal hydroxide composite material, which comprises microbeads and a layered composite metal hydroxide coated on the surface of the microbeads;
[0006] The interlayer anions of the layered composite metal hydroxide are corrosion-inhibiting anions.
[0007] Preferably, the microbeads are glass microbeads and / or ceramic microbeads.
[0008] Preferably, the particle size of the microbeads is 0.1-500 μm, more preferably 50-150 μm.
[0009] Preferably, the corrosion-inhibiting anion is selected from MoO4 2- PO4 3- HCOO - 、CH3(CH2) 11 OSO3 - 、NO3 - and NO2 - One or more of the following.
[0010] Preferably, the metal elements in the layered composite metal hydroxide are metal M and metal N; the metal M is selected from one or more of Mg, Ni, Cu, Zn and Ca, and the metal N is selected from one or more of Al, Co, Fe, Cr and Ga.
[0011] The second aspect of the present invention provides a method for preparing a microsphere layered composite metal hydroxide composite material, the method comprising the following steps:
[0012] (1) mixing microbeads, a metal precursor, a solvent, and a substance capable of forming carbonate ions in a solution to obtain a mixed solution, adjusting the pH value of the mixed solution to greater than 7, and then reacting;
[0013] (2) performing solid-liquid separation and heat treatment on the material obtained in step (1);
[0014] (3) Mixing the material obtained by heat treatment in step (2) with a solution containing a corrosion-inhibiting compound, adjusting the pH value of the solution to greater than 7, and then reacting.
[0015] Preferably, the microbeads are glass microbeads and / or ceramic microbeads.
[0016] Preferably, the particle size of the microbeads is 0.1-500 μm, more preferably 50-150 μm.
[0017] Preferably, the metal precursor is a metal M precursor and a metal N precursor; the metal M is selected from one or more of Mg, Ni, Cu, Zn and Ca, and the metal N is selected from one or more of Al, Co, Fe, Cr and Ga.
[0018] Preferably, the molar ratio of the metal M precursor to the metal N precursor is 1:0.2-5, calculated as metal.
[0019] Preferably, the weight ratio of the microbeads to the metal M precursor is 1:0.5-5.
[0020] Preferably, in step (2), the heat treatment conditions include: temperature of 550-650° C. and time of 3-8 h.
[0021] Preferably, in step (3), the corrosion-inhibiting anion is selected from MoO4 2- PO4 3- HCOO - 、CH3(CH2) 11 OSO3 - 、NO3 - and NO2 - One or more of the following.
[0022] The third aspect of the present invention provides a micro-bead layered composite metal hydroxide composite material prepared by the above method.
[0023] A fourth aspect of the present invention provides an application of a microsphere layered composite metal hydroxide composite material in an anti-corrosion coating.
[0024] Compared with the prior art, the technical solution of the present invention has the following advantages:
[0025] (1) The microbead layered composite metal hydroxide composite material of the present invention has good dispersibility and good performance in capturing corrosive anions such as chloride ions;
[0026] (2) In the present invention, the glass microspheres or ceramic microspheres have a heat-insulating property. Therefore, when the microsphere layered composite metal hydroxide composite material is used in an anti-corrosion coating, it can not only improve the anti-corrosion performance of the anti-corrosion coating, but also the anti-corrosion coating has a heat-insulating effect;
[0027] (3) The preparation method of the microbead layered composite metal hydroxide composite material described in the present invention is simple, green and environmentally friendly; moreover, the method described in the present invention forms a microbead layered composite metal hydroxide composite material by preferentially introducing carbonate anions, and the interlayer anions are carbonates, and the carbonates are decomposed by heat treatment to reserve holes, thereby any desired corrosion-inhibiting anions can be introduced, and there are no requirements for the anions of the metal precursor. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 is a scanning electron microscope image and a scanning electron microscope energy spectrum image of the microbead layered composite metal hydroxide composite material prepared in Example 1;
[0029] Figure 2 is the XRD spectrum of the microbead layered composite metal hydroxide composite material prepared in Example 1, the intermediate material prepared in Example 1, and silicon dioxide;
[0030] Figure 3 It is the FTIR of the microbead layered composite metal hydroxide composite material prepared in Example 1, the intermediate material prepared in Example 1, and silicon dioxide;
[0031] Figure 4 The graph is a trend graph of chloride ion concentration in the solution after the products obtained in Example 1 and Comparative Example 1 were mixed with 100 mmol / L NaCl solution at different times. DETAILED DESCRIPTION
[0032] The specific implementation of the present invention is described in detail below in conjunction with the accompanying drawings. It should be understood that the specific implementation described here is only used to illustrate and explain the present invention, and is not used to limit the present invention.
[0033] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0034] In one aspect, the present invention provides a microbead layered composite metal hydroxide composite material, the composite material comprising microbeads and a layered composite metal hydroxide coated on the surface of the microbeads;
[0035] The interlayer anions of the layered composite metal hydroxide are corrosion-inhibiting anions.
[0036] In the present invention, there is no special requirement for the “microbeads”, and both “hollow microbeads” and “solid microbeads” are acceptable.
[0037] In a preferred embodiment, the microbeads are glass microbeads and / or ceramic microbeads.
[0038] In a preferred embodiment, in order to further improve the dispersibility of the layered composite metal hydroxide, the particle size of the microbeads is 0.1-500 μm, more preferably 50-150 μm.
[0039] In the present invention, the "corrosion-inhibiting anions" refer to "ions that can undergo ion exchange with corrosive anions (such as chloride ions) and capture corrosive anions in the environment."
[0040] In a preferred embodiment, in order to further improve the performance of the layered composite metal hydroxide in capturing corrosive anions (such as chloride ions), the corrosion-inhibiting anions are selected from MoO4 2- PO4 3- HCOO- 、CH3(CH2) 11 OSO3 - 、NO3 - and NO2 - One or more of the following.
[0041] In a preferred embodiment, the metal elements in the layered composite metal hydroxide are metal M and metal N; the metal M is selected from one or more of Mg, Ni, Cu, Zn and Ca, and the metal N is selected from one or more of Al, Co, Fe, Cr and Ga; specifically, the layered composite metal hydroxide can be Mg-Al layered composite metal hydroxide, Mg-Al / Co layered composite metal hydroxide, Mg-Fe layered composite metal hydroxide, Mg-Co layered composite metal hydroxide, Mg-Al / Co / Fe layered composite metal hydroxide, Ni-Al layered composite metal hydroxide, Ni-Fe layered composite metal hydroxide, Ni-Al / Co / Fe / Cr / Ga layered composite metal hydroxide, Cu-Al / Co / Fe / Cr layered composite metal hydroxide or Zn-Al / Co / Fe / Cr layered composite metal hydroxide.
[0042] The microbead layered composite metal hydroxide composite material of the present invention has good dispersibility and the ability to capture corrosive anions (such as chloride ions) by coating the layered composite metal hydroxide on the surface of the microbead, and has good application in anti-corrosion coatings. This may be because the microbeads improve the dispersibility of the layered composite metal hydroxide and improve the stacking problem of the layered composite metal hydroxide, thereby increasing the specific surface area of the layered composite metal hydroxide and improving its efficiency in capturing corrosive anions (such as chloride ions).
[0043] The second aspect of the present invention provides a method for preparing a microsphere layered composite metal hydroxide composite material, the method comprising the following steps:
[0044] (1) mixing microbeads, a metal precursor, a solvent, and a substance capable of forming carbonate ions in a solution to obtain a mixed solution, adjusting the pH value of the mixed solution to greater than 7, and then reacting;
[0045] (2) performing solid-liquid separation and heat treatment on the material obtained in step (1);
[0046] (3) Mixing the material obtained by heat treatment in step (2) with a solution containing a corrosion-inhibiting compound, adjusting the pH value of the solution to greater than 7, and then reacting.
[0047] In a preferred embodiment, the method further comprises pre-treating the microbeads to remove grease on the surface of the microbeads.
[0048] In a specific embodiment, the microbeads are mixed with ethanol and then stirred, and then filtered, washed and dried after stirring.
[0049] In a preferred embodiment, the microbeads are glass microbeads and / or ceramic microbeads.
[0050] In a preferred embodiment, in order to further improve the dispersibility of the layered composite metal hydroxide, the particle size of the microbeads is 0.1-500 μm, more preferably 50-150 μm.
[0051] In a preferred embodiment, the metal precursors are metal M precursors and metal N precursors; the metal M is selected from one or more of Mg, Ni, Cu, Zn and Ca, and the metal N is selected from one or more of Al, Co, Fe, Cr and Ga.
[0052] In a preferred embodiment, the metal M precursor is one or more of a soluble magnesium salt, a soluble nickel salt, a soluble copper salt, a soluble zinc salt and a soluble calcium salt; the metal N precursor is one or more of a soluble aluminum salt, a soluble cobalt salt, a soluble iron salt, a soluble chromium salt and a soluble gallium salt; specifically, the metal M precursor may be one or two or more of magnesium nitrate, magnesium nitrate hexahydrate, nickel nitrate, nickel nitrate hexahydrate, copper nitrate, copper chloride, copper sulfate, zinc nitrate and calcium nitrate; the metal N precursor may be one or more of aluminum nitrate, aluminum nitrate nonahydrate, cobalt nitrate, cobalt nitrate hexahydrate, iron nitrate, iron nitrate nonahydrate, chromium nitrate and gallium nitrate.
[0053] In a preferred embodiment, in order to improve the stability of the layered composite metal hydroxide, the molar ratio of the metal M precursor to the metal N precursor is 1:0.2-5, calculated as metal; specifically, it can be 1:0.2, 1:0.45, 1:0.5, 1:0.6, 1:0.7, 1:0.8, 1:0.9, 1:1, 1:2, 1:3, 1:4 or 1:5.
[0054] In a preferred embodiment, in order to further improve the dispersibility of the layered composite metal hydroxide, the weight ratio of the microbeads to the metal M precursor is 1:0.5-5, more preferably 1:1.
[0055] In the present invention, there is no special requirement for the “substance capable of forming carbonate ions in a solution”, as long as it can provide carbonate ions in a solution.
[0056] In a preferred embodiment, the substance capable of forming carbonate ions in the solution may be carbonate, bicarbonate or carbonic acid; specifically, it may be one or more of sodium carbonate, potassium carbonate, ammonium carbonate, sodium bicarbonate and potassium bicarbonate.
[0057] In the present invention, there is no special requirement for the amount of the substance capable of forming carbonate ions in the solution, as long as microbead layered composite metal hydroxide can be obtained after solid-liquid separation in step (2) and the interlayer anions are carbonate.
[0058] In a preferred embodiment, the molar ratio of the metal M precursor (measured in metal M) to the substance capable of forming carbonate ions in solution is 1:0.5-3, more preferably 1:1. The above amount can not only improve the stability of the layered composite metal hydroxide but also will not cause waste of the raw material capable of forming carbonate ions in solution.
[0059] In a preferred embodiment, in order to improve the efficiency of the reaction and accelerate the formation rate of the layered composite metal hydroxide, in step (1), the pH value of the mixed solution is adjusted to ≥ 8, more preferably, the pH value of the mixed solution is adjusted to 9-10; specifically, it can be 9, 9.5 or 10.
[0060] In a preferred embodiment, in step (2), the heat treatment conditions include: a temperature of 550-650°C and a time of 3-8h; specifically, the temperature may be 550°C, 600°C or 650°C; and the time may be 3h, 4h, 5h, 6h, 7h or 8h.
[0061] In a preferred embodiment, in order to further improve the performance of the layered composite metal hydroxide in capturing corrosive anions (such as chloride ions), in step (3), the corrosion-inhibiting anion is selected from MoO4 2- PO4 3- HCOO - 、CH3(CH2) 11 OSO3 - 、NO3 - and NO2 - One or more of the following.
[0062] In a preferred embodiment, in order to improve the efficiency of the reaction, in step (3), the pH value of the solution is adjusted to ≥ 8, more preferably, the pH value of the solution is adjusted to 9-10; specifically, it can be 9, 9.5 or 10.
[0063] In the present invention, the "corrosion-inhibiting compound" refers to a "substance capable of providing corrosion-inhibiting anions".
[0064] In the present invention, there is no special requirement for the amount of the corrosion-inhibiting compound, as long as micro-bead layered composite metal hydroxide can be obtained after the reaction in step (3) and the interlayer anions are corrosion-inhibiting anions.
[0065] In a preferred embodiment, the molar ratio of the metal M precursor (measured in metal M) to the corrosion-inhibiting compound is 1:0.5-2, more preferably 1:1. The above amount can not only further improve the performance of the layered composite metal hydroxide in capturing corrosive anions (such as chloride ions) but also will not cause waste of the raw material corrosion-inhibiting compound.
[0066] In a specific embodiment, the process of step (1) includes: mixing microbeads, a substance capable of forming carbonate ions in a solution, and water, named solution A, then mixing a metal precursor and water, named solution B, adding solution B to solution A, adjusting the pH value of the mixed solution to ≥8 during the addition process, stirring and reacting.
[0067] In a specific embodiment, the process of step (2) includes: filtering and washing the material obtained in step (1), and then heat treating the obtained solid phase product at 550-650° C. for 3-8 hours.
[0068] In a specific embodiment, the process of step (3) includes: mixing the material obtained in step (2) with a solution containing a corrosion-inhibiting compound, adjusting the pH value of the solution to ≥ 8, stirring and reacting, and then filtering, washing and drying.
[0069] According to the method of the present invention, the intermediate product obtained by solid-liquid separation in step (2) is a micro-bead layered composite metal hydroxide and the interlayer anions are carbonate ions. After the intermediate product is heat treated, the interlayer anions carbonate ions will decompose and reserve holes, thereby introducing any desired corrosion-inhibiting anions into the layered composite metal hydroxide. Since the carbonate ions and the cationic layer of the layered composite metal hydroxide have a strong binding force, there is no special requirement for the anions of the metal precursor when preparing the micro-bead layered composite metal hydroxide composite material according to the method of the present invention.
[0070] The third aspect of the present invention provides a micro-bead layered composite metal hydroxide composite material prepared by the above method.
[0071] A fourth aspect of the present invention provides an application of a microsphere layered composite metal hydroxide composite material in an anti-corrosion coating.
[0072] The following examples further illustrate the microbead layered composite metal hydroxide composite material and its preparation method and application. The examples are implemented based on the technical solution of the present invention, and provide detailed implementation methods and specific operation processes, but the protection scope of the present invention is not limited to the following examples.
[0073] Example 1
[0074] (1) Ceramic microbeads and ethanol were mixed and stirred, and then filtered, washed and dried after stirring for 30 minutes. 100 mg of ceramic microbeads with a particle size of 100-150 μm after drying were dispersed in 50 mL of water, stirred at 150 r / min for 30 minutes, and after uniform dispersion, 0.1 g of anhydrous sodium carbonate was added, and ultrasonic treatment was performed at 500 W for 5 minutes to obtain solution A1; 0.25 g of magnesium nitrate hexahydrate and 0.18 g of aluminum nitrate nonahydrate were dispersed in 20 mL of water, and ultrasonic treatment was performed at 500 W for 10 minutes to obtain solution B1; solution B1 was slowly added dropwise to solution A1 for 20 minutes, and a 1 M sodium hydroxide solution was added dropwise at the same time to adjust the pH value of the mixed solution to 9, and then reacted. After the addition was completed, the mixture was stirred at 150 r / min for 60 minutes;
[0075] (2) filtering and washing the material obtained in step (1) to obtain an intermediate material S1 (SiO2@Mg-AlCO3), and then heat-treating the intermediate material S1 at 550°C under vacuum for 8h;
[0076] (3) The material obtained in step (2) is dispersed in 50 mL of a 3 mg / mL sodium nitrite solution, the pH value of the solution is adjusted to 9, and then reacted, stirred at 150 r / min for 5 h, and then filtered, washed and dried to obtain the final product, ceramic microbead Mg-Al layered composite metal hydroxide composite material M1 (SiO2@Mg-Al NO2).
[0077] Example 2
[0078] (1) Ceramic microbeads and ethanol were mixed and stirred, and then filtered, washed and dried after stirring for 30 minutes. 50g of ceramic microbeads with a particle size of 75-150μm after drying were dispersed in 1L of water, stirred at 300r / min for 60min, and after uniform dispersion, 50g of anhydrous sodium carbonate was added, and ultrasonic treatment was performed at 800W power for 10min to obtain solution A2; 120g of magnesium nitrate hexahydrate and 100g of aluminum nitrate nonahydrate were dispersed in 200mL of water, and ultrasonic treatment was performed at 800W power for 20min to obtain solution B2; solution B2 was slowly added dropwise to solution A2 for 120min, and a sodium hydroxide solution with a concentration of 1M was added dropwise at the same time to adjust the pH value of the mixed solution to 9, and then reacted. After the addition was completed, the mixture was stirred at a low speed for 3h;
[0079] (2) filtering and washing the material obtained in step (1) to obtain an intermediate material S2 (SiO2@Mg-AlCO3), and then heat-treating the intermediate material S2 at 650°C under vacuum conditions for 5 hours;
[0080] (3) The material obtained in step (2) is dispersed in 1L of a sodium nitrite solution with a concentration of 100g / L, the pH value of the solution is adjusted to 9, and then reacted, stirred at 300r / min for 5h, and then filtered, washed and dried to obtain the final product, ceramic microbead Mg-Al layered composite metal hydroxide composite material M2 (SiO2@Mg-Al NO2).
[0081] Example 3
[0082] (1) Ceramic microbeads and ethanol were mixed and stirred, and then filtered, washed and dried after stirring for 30 minutes. 5 g of ceramic microbeads with a particle size of 200-250 μm after drying were dispersed in 200 mL of water, stirred at 150 r / min for 60 minutes, and after uniform dispersion, 5 g of anhydrous sodium carbonate was added, and ultrasonic treatment was performed at 500 W for 10 minutes to obtain solution A3; 10 g of magnesium nitrate hexahydrate, 1 g of cobalt nitrate and 15 g of aluminum nitrate nonahydrate were dispersed in 50 mL of water, and ultrasonic treatment was performed at 500 W for 10 minutes to obtain solution B3; solution B3 was slowly added dropwise to solution A3 for 50 minutes, and a 1 M sodium hydroxide solution was added dropwise at the same time to adjust the pH value of the mixed solution to 9, and then reacted. After the addition was completed, stirring was performed at 150 r / min for 1 hour;
[0083] (2) filtering and washing the material obtained in step (1) to obtain an intermediate material S3 (SiO2@Mg-AlCO3), and then heat-treating the intermediate material S3 at 600°C under vacuum conditions for 7h;
[0084] (3) The material obtained in step (2) is dispersed in 100 mL of a sodium nitrite solution having a concentration of 0.1 g / mL, the pH value of the solution is adjusted to 10, and then the mixture is reacted and stirred at 200 r / min for 5 h, and then filtered, washed and dried to obtain the final product, ceramic microbead Co-doped Mg-Al layered composite metal hydroxide composite material M3 (SiO2@Mg-Al / Co NO2).
[0085] Example 4
[0086] (1) Ceramic microbeads and ethanol were mixed and stirred, and then filtered, washed and dried after stirring for 30 minutes. 200 mg of ceramic microbeads with a particle size of 200-300 μm after drying were dispersed in 100 mL of water, stirred at 200 r / min for 60 minutes, and after uniform dispersion, 0.1 g of anhydrous sodium carbonate was added, and ultrasonic treatment was performed at 800 W for 10 minutes to obtain solution A4; 0.5 g of magnesium nitrate hexahydrate and 2 g of aluminum nitrate nonahydrate were dispersed in 50 mL of water, and ultrasonic treatment was performed at 800 W for 20 minutes to obtain solution B4; solution B4 was slowly added dropwise to solution A4 for 40 minutes, and a sodium hydroxide solution with a concentration of 1 M was simultaneously added dropwise to adjust the pH value of the mixed solution to 8, and then reacted. After the addition was completed, stirring was performed at 200 r / min for 30 minutes;
[0087] (2) filtering and washing the material obtained in step (1) to obtain an intermediate material S4 (SiO2@Mg-AlCO3), and then heat-treating the intermediate material S4 at 600°C under vacuum conditions for 10 hours;
[0088] (3) The material obtained in step (2) is dispersed in 100 mL of a 6 mg / mL sodium nitrite solution, the pH value of the solution is adjusted to 10, and then the reaction is carried out, stirred at 200 r / min for 10 h, and then filtered, washed and dried to obtain the final product, ceramic microbead Mg-Al layered composite metal hydroxide composite material M4 (SiO2@Mg-Al NO2).
[0089] Example 5
[0090] (1) Ceramic microbeads and ethanol were mixed and stirred, and then filtered, washed and dried after stirring for 30 minutes. 50 mg of ceramic microbeads with a particle size of 30-50 μm after drying were dispersed in 25 mL of water, stirred at 100 r / min for 10 minutes, and after uniform dispersion, 500 mg of anhydrous sodium carbonate was added, and ultrasonicated at 500 W for 5 minutes to obtain solution A5; 0.01 g of magnesium nitrate hexahydrate and 0.01 g of aluminum nitrate nonahydrate were dispersed in 10 mL of water, and ultrasonicated at 250 W for 5 minutes to obtain solution B5; solution B5 was slowly added dropwise to solution A5 for 10 minutes, and a 1 M sodium hydroxide solution was added dropwise at the same time to adjust the pH value of the mixed solution to 8, and then reacted. After the addition was completed, the mixture was stirred at 100 r / min for 30 minutes;
[0091] (2) filtering and washing the material obtained in step (1) to obtain an intermediate material S5 (SiO2@Mg-AlCO3), and then heat-treating the intermediate material S5 at 500°C under vacuum for 6 hours;
[0092] (3) The material obtained in step (2) is dispersed in 20 mL of a 1.5 mg / mL sodium nitrite solution, the pH value of the solution is adjusted to 8, and then reacted, stirred at 100 r / min for 3 h, and then filtered, washed and dried to obtain the final product, ceramic microbead Mg-Al layered composite metal hydroxide composite material M5 (SiO2@Mg-Al NO2).
[0093] Example 6
[0094] (1) Ceramic microbeads and ethanol were mixed and stirred, and then filtered, washed and dried after stirring for 30 minutes. 100 mg of ceramic microbeads with a particle size of 150-200 μm after drying were dispersed in 50 mL of water, stirred at 150 r / min for 30 minutes, and after uniform dispersion, 10 mg of anhydrous sodium carbonate was added, and ultrasonicated at 600 W for 8 minutes to obtain solution A6; 10 mg of magnesium nitrate hexahydrate and 50 mg of aluminum nitrate nonahydrate were dispersed in 30 mL of water, and ultrasonicated at 600 W for 15 minutes to obtain solution B6; solution B6 was slowly added dropwise to solution A6 for 30 minutes, and a 1 M sodium hydroxide solution was added dropwise at the same time to adjust the pH value of the mixed solution to 12, and then reacted. After the addition was completed, the mixture was stirred at 150 r / min for 60 minutes;
[0095] (2) filtering and washing the material obtained in step (1) to obtain an intermediate material S6 (SiO2@Mg-AlCO3), and then heat-treating the intermediate material S6 at 500°C under vacuum for 9 hours;
[0096] (3) The material obtained in step (2) is dispersed in 75 mL of a sodium nitrite solution having a concentration of 4.5 mg / mL, the pH value of the solution is adjusted to 9.5, and then reacted, stirred at 150 r / min for 8 h, and then filtered, washed and dried to obtain the final product, ceramic microbead Mg-Al layered composite metal hydroxide composite material M6 (SiO2@Mg-Al NO2).
[0097] Example 7
[0098] (1) Ceramic microbeads and ethanol were mixed and stirred, and then filtered, washed and dried after stirring for 30 minutes. 250 mg of ceramic microbeads with a particle size of 250-300 μm after drying were dispersed in 125 mL of water, stirred at 200 r / min for 45 minutes, and after uniform dispersion, 0.25 g of anhydrous sodium carbonate was added, and ultrasonic treatment was performed at 500 W for 12 minutes to obtain solution A7; 0.625 g of magnesium nitrate hexahydrate and 0.45 g of ferric nitrate nonahydrate were dispersed in 50 mL of water, and ultrasonic treatment was performed at 500 W for 25 minutes to obtain solution B7; solution B7 was slowly added dropwise to solution A7 for 50 minutes, and a sodium hydroxide solution with a concentration of 1 M was simultaneously added dropwise to adjust the pH value of the mixed solution to 8, and then reacted. After the addition was completed, the mixture was stirred at 200 r / min for 90 minutes;
[0099] (2) filtering and washing the material obtained in step (1) to obtain an intermediate material S7 (SiO2@Mg-FeCO3), and then heat-treating the intermediate material S7 at 550°C under vacuum conditions for 10 hours;
[0100] (3) The material obtained in step (2) is dispersed in 100 mL of a 3 mg / mL sodium nitrite solution, the pH value of the solution is adjusted to 8, and then the reaction is carried out, stirred at 200 r / min for 1 hour, and then filtered, washed and dried to obtain the final product, ceramic microbead Mg-Fe layered composite metal hydroxide composite material M7 (SiO2@Mg-Fe NO2).
[0101] Example 8
[0102] (1) Ceramic microbeads and ethanol were mixed and stirred, and then filtered, washed and dried after stirring for 30 minutes. 300 mg of ceramic microbeads with a particle size of 300-400 μm after drying were dispersed in 100 mL of water, stirred at 250 r / min for 50 minutes, and after uniform dispersion, 0.05 g of anhydrous sodium carbonate was added, and ultrasonic treatment was performed at 500 W for 15 minutes to obtain solution A8; 0.05 g of nickel nitrate hexahydrate and 0.05 g of aluminum nitrate nonahydrate were dispersed in 60 mL of water, and ultrasonic treatment was performed at 500 W for 30 minutes to obtain solution B8; solution B8 was slowly added dropwise to solution A8 for 60 minutes, and a 3 M sodium hydroxide solution was added dropwise at the same time to adjust the pH value of the mixed solution to 12, and then reacted. After the addition was completed, the mixture was stirred at 250 r / min for 100 minutes;
[0103] (2) filtering and washing the material obtained in step (1) to obtain an intermediate material S8 (SiO2@Ni-AlCO3), and then heat-treating the intermediate material S8 at 650°C under vacuum conditions for 6 hours;
[0104] (3) The material obtained in step (2) is dispersed in 150 mL of a 50 mg / mL sodium nitrite solution, the pH value of the solution is adjusted to 11, and then reacted, stirred at 250 r / min for 5 h, and then filtered, washed and dried to obtain the final product, ceramic microbead Ni-Al layered composite metal hydroxide composite material M8 (SiO2@Ni-Al NO2).
[0105] Example 9
[0106] (1) Ceramic microbeads and ethanol were mixed and stirred, and then filtered, washed and dried after stirring for 30 minutes. 400 mg of ceramic microbeads with a particle size of 400-500 μm after drying were dispersed in 200 mL of water, stirred at 300 r / min for 60 minutes, and after uniform dispersion, 0.1 g of anhydrous sodium carbonate was added, and ultrasonic treatment was performed at 500 W power for 20 minutes to obtain solution A9; 1 g of nickel nitrate hexahydrate and 0.72 g of ferric nitrate nonahydrate were dispersed in 80 mL of water, and ultrasonic treatment was performed at 500 W power for 40 minutes to obtain solution B9; solution B9 was slowly added dropwise to solution A9 for 80 minutes, and a 2 M sodium hydroxide solution was added dropwise at the same time to adjust the pH value of the mixed solution to 12, and then reacted. After the addition was completed, stirring was performed at 300 r / min for 120 minutes;
[0107] (2) filtering and washing the material obtained in step (1) to obtain an intermediate material S9 (SiO2@Ni-FeCO3), and then heat-treating the intermediate material S9 at 500°C under vacuum for 4 hours;
[0108] (3) The material obtained in step (2) is dispersed in 200 mL of a 5 mg / mL sodium molybdate solution, the pH value of the solution is adjusted to 10, and then reacted, stirred at 300 r / min for 2 h, and then filtered, washed and dried to obtain the final product, ceramic microbead Ni-Fe layered composite metal hydroxide composite material M9 (SiO2@Ni-Fe MoO4).
[0109] Example 10
[0110] (1) Ceramic microbeads and ethanol were mixed and stirred, and then filtered, washed and dried after stirring for 30 minutes. 500 mg of ceramic microbeads with a particle size of 500-600 μm after drying were dispersed in 250 mL of water, stirred at 350 r / min for 70 minutes, and after uniform dispersion, 0.5 g of anhydrous sodium carbonate was added, and ultrasonic treatment was performed at 1000 W power for 30 minutes to obtain solution A10; 2 g of magnesium nitrate hexahydrate and 2 g of aluminum nitrate nonahydrate were dispersed in 100 mL of water, and ultrasonic treatment was performed at 2000 W power for 60 minutes to obtain solution B10; solution B10 was slowly added dropwise to solution A10 for 100 minutes, and a sodium hydroxide solution with a concentration of 1 M was simultaneously added dropwise to adjust the pH value of the mixed solution to 8, and then reacted. After the addition was completed, stirring was performed at 350 r / min for 140 minutes;
[0111] (2) filtering and washing the material obtained in step (1) to obtain an intermediate material S10 (SiO2@Mg-AlCO3), and then heat-treating the intermediate material S10 at 550°C under vacuum for 6 hours;
[0112] (3) The material obtained in step (2) is dispersed in 250 mL of a sodium phosphate solution having a concentration of 15 mg / mL, the pH value of the solution is adjusted to 10, and then reacted, stirred at 350 r / min for 3 h, and then filtered, washed and dried to obtain the final product, ceramic microbead Mg-Al layered composite metal hydroxide composite material M10 (SiO2@Mg-Al PO4).
[0113] Embodiment 11
[0114] (1) Ceramic microbeads and ethanol were mixed and stirred, and then filtered, washed and dried after stirring for 30 minutes. 100 mg of ceramic microbeads with a particle size of 100-150 μm after drying were dispersed in 50 mL of water, stirred at 150 r / min for 30 minutes, and after uniform dispersion, 0.1 g of anhydrous sodium carbonate was added, and ultrasonic treatment was performed at 500 W for 5 minutes to obtain solution A1; 2 g of magnesium nitrate hexahydrate and 0.18 g of aluminum nitrate nonahydrate were dispersed in 20 mL of water, and ultrasonic treatment was performed at 500 W for 10 minutes to obtain solution B11; solution B11 was slowly added dropwise to solution A1 for 20 minutes, and a 1 M sodium hydroxide solution was added dropwise at the same time to adjust the pH value of the mixed solution to 9, and then reacted. After the addition was completed, the mixture was stirred at 150 r / min for 60 minutes;
[0115] (2) filtering and washing the material obtained in step (1) to obtain an intermediate material S11 (SiO2@Mg-AlCO3), and then heat-treating the intermediate material S1 at 550°C under vacuum for 8h;
[0116] (3) The material obtained in step (2) is dispersed in 50 mL of a 3 mg / mL sodium nitrite solution, the pH value of the solution is adjusted to 9, and then the reaction is carried out, stirred at 150 r / min for 5 h, and then filtered, washed and dried to obtain the final product, ceramic microbead Mg-Al layered composite metal hydroxide composite material M11 (SiO2@Mg-Al NO2).
[0117] Example 12
[0118] (1) Ceramic microbeads and ethanol were mixed and stirred, and then filtered, washed and dried after stirring for 30 minutes. 100 mg of ceramic microbeads with a particle size of 100-150 μm after drying were dispersed in 50 mL of water, stirred at 150 r / min for 30 minutes, and after uniform dispersion, 0.1 g of anhydrous sodium carbonate was added, and ultrasonic treatment was performed at 500 W for 5 minutes to obtain solution A1; 0.25 g of magnesium nitrate hexahydrate and 0.18 g of aluminum nitrate nonahydrate were dispersed in 20 mL of water, and ultrasonic treatment was performed at 500 W for 10 minutes to obtain solution B1; solution B1 was slowly added dropwise to solution A1 for 20 minutes, and a 1 M sodium hydroxide solution was added dropwise at the same time to adjust the pH value of the mixed solution to 13, and then reacted. After the addition was completed, stirring was performed at 150 r / min for 60 minutes;
[0119] (2) filtering and washing the material obtained in step (1) to obtain an intermediate material S12 (SiO2@Mg-AlCO3), and then heat-treating the intermediate material S1 at 550°C under vacuum for 8h;
[0120] (3) The material obtained in step (2) is dispersed in 50 mL of a 3 mg / mL sodium nitrite solution, the pH value of the solution is adjusted to 13, and then reacted, stirred at 150 r / min for 5 h, and then filtered, washed and dried to obtain the final product, ceramic microbead Mg-Al layered composite metal hydroxide composite material M12 (SiO2@Mg-Al NO2).
[0121] Comparative Example 1
[0122] The process is carried out in the same manner as in Example 1, except that in step (1), no ceramic microbeads are added to obtain Mg-Al layered composite metal hydroxide N1 (Mg-Al NO2).
[0123] Test Case
[0124] (1) Characterize silicon dioxide (SiO2) and the intermediate material and final product obtained in Example 1, Figure 1 is a scanning electron microscope image and a scanning electron microscope energy spectrum image of the microbead layered composite metal hydroxide composite material prepared in Example 1; Figure 2is the XRD spectrum of the microbead layered composite metal hydroxide composite material prepared in Example 1, the intermediate material prepared in Example 1, and silicon dioxide; Figure 3 It is the FTIR of the microbead layered composite metal hydroxide composite material prepared in Example 1, the intermediate material prepared in Example 1, and silicon dioxide.
[0125] Depend on Figure 1 It can be seen that the microbead layered composite metal hydroxide composite material (SiO2@Mg-Al NO2) prepared in Example 1 contains Mg, Al, N, O and Si elements, and the Mg and Al elements are evenly distributed; Figure 2 It can be seen that Example 1 successfully prepared a micro-bead layered composite metal hydroxide composite material (SiO2@Mg-AlNO2); Figure 3 It can be seen that the interlayer anions of the microbead layered composite metal hydroxide composite material (SiO2@Mg-AlNO2) prepared in Example 1 are completely replaced by nitrite ions from carbonate ions.
[0126] (2) The performance of the products obtained in Examples 1-12 and Comparative Example 1 in capturing chloride ions was tested. The test method was as follows: the same weight of the sample to be tested was weighed and dispersed in the same volume of a NaCl solution with a concentration of 100 mmol / L. The chloride ion concentration in the solution was measured using an automatic titrator after 180 min. The test results are shown in Table 1. Figure 4 The graph is a trend graph of chloride ion concentration in the solution after the products obtained in Example 1 and Comparative Example 1 were mixed with 100 mmol / L NaCl solution at different times.
[0127] Table 1
[0128] serial number <![CDATA[Cl - Concentration (mmol / L)]]> serial number <![CDATA[Cl - Concentration (mmol / L)]]> Example 1 60.05 Example 8 68.24 Example 2 61.28 Example 9 64.19 Example 3 60.39 Example 10 65.30 Example 4 68.88 Embodiment 11 78.59 Example 5 65.29 Example 12 76.3 Example 6 70.02 Comparative Example 1 70.29 Example 7 64.09
[0129] Depend on Figure 4 It can be seen that throughout the process, the ability of the microbead layered composite metal hydroxide composite material prepared in Example 1 to capture chloride ions is greater than the ability of the layered composite metal hydroxide prepared in Comparative Example 1 to capture chloride ions; from the results in Table 1, it can be seen that the microbead layered composite metal hydroxide composite material described in the present invention has excellent ability to capture chloride ions, especially the microbead layered composite metal hydroxide composite material prepared in Examples 1-3 has better performance in capturing chloride ions. Therefore, the microbead layered composite metal hydroxide composite material described in the present invention has a good application prospect in anti-corrosion coatings.
[0130] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A microsphere layered composite metal hydroxide composite material, characterized in that: The composite material comprises microbeads and layered composite metal hydroxides coated on the surface of the microbeads; The interlayer anions of the layered composite metal hydroxide are corrosion-inhibiting anions.
2. The microsphere layered composite metal hydroxide composite material according to claim 1, characterized in that: The microbeads are glass microbeads and / or ceramic microbeads; Preferably, the particle size of the microbeads is 0.1-500 μm, more preferably 50-150 μm.
3. The microsphere layered composite metal hydroxide composite material according to claim 1 or 2, characterized in that: The corrosion-inhibiting anion is selected from MoO4 2- PO4 3- HCOO - 、CH3(CH2) 11 OSO3 - 、NO3 - and NO2 - One or more of the following.
4. The microsphere layered composite metal hydroxide composite material according to any one of claims 1 to 3, characterized in that: The metal elements in the layered composite metal hydroxide are metal M and metal N; The metal M is selected from one or more of Mg, Ni, Cu, Zn and Ca, and the metal N is selected from one or more of Al, Co, Fe, Cr and Ga.
5. A method for preparing a microsphere layered composite metal hydroxide composite material, characterized in that: The method comprises the following steps: (1) mixing microbeads, a metal precursor, a solvent, and a substance capable of forming carbonate ions in a solution to obtain a mixed solution, adjusting the pH value of the mixed solution to greater than 7, and then reacting; (2) performing solid-liquid separation and heat treatment on the material obtained in step (1); (3) Mixing the material obtained by heat treatment in step (2) with a solution containing a corrosion-inhibiting compound, adjusting the pH value of the solution to greater than 7, and then reacting.
6. The method according to claim 5, characterized in that The microbeads are glass microbeads and / or ceramic microbeads; Preferably, the particle size of the microbeads is 0.1-500 μm, more preferably 50-150 μm.
7. The method according to claim 5 or 6, characterized in that: The metal precursors are metal M precursors and metal N precursors; The metal M is selected from one or more of Mg, Ni, Cu, Zn and Ca, and the metal N is selected from one or more of Al, Co, Fe, Cr and Ga.
8. The method according to claim 7, characterized in that The molar ratio of the metal M precursor to the metal N precursor is 1:0.2-5, calculated as metal.
9. The method according to claim 7 or 8, characterized in that: The weight ratio of the microbeads to the metal M precursor is 1:0.5-5.
10. The method according to any one of claims 5 to 9, characterized in that: In step (2), the heat treatment conditions include: temperature of 550-650° C. and time of 3-8 h.
11. The method according to any one of claims 5 to 10, characterized in that: In step (3), the corrosion-inhibiting anion is selected from MoO4 2- PO4 3- HCOO - 、CH3(CH2) 11 OSO3 - 、NO3 - and NO2 - One or more of the following.
12. A micro-bead layered composite metal hydroxide composite material prepared by the method according to any one of claims 5 to 11.
13. Use of the microsphere layered composite metal hydroxide composite material according to any one of claims 1 to 4 or the microsphere layered composite metal hydroxide composite material according to claim 12 in anti-corrosion coatings.